The Pemikiran Pendidikan Akhlak Tasawuf dalam Ajaran Tarekat Qadiriyyah wa Naqsyabandiyyah Suryalaya: Pendidikan Akhlak Tasawuf - Syukur, Agus; Rosyada, Dede (Journal of Sufism and Psychotherapy, 2023)
The Qadariyah Naqsabandiyah Suryalaya Order also teaches about Sufism moral education which has an important role in human life. Even with Sufism morals, humans will be aware of the existence of a dhahir relationship between themselves and God, which previously was only considered to have an inner relationship. The type of research in this article is qualitative research. The aim of this research is to reveal the values of Sufism moral education thought in the teachings of the Qadiriyyah wa Naqsyabandiyyah Suryalaya order. The data collection method is by literature study. The results of this research reveal several points of thought in the teachings of the Tarekat Qadiriyyah wa Naqsyabandiyyah Suryalaya regarding the formation of noble morals: 1). The essence of implementing the Prophet's sunnah is the actualization of dhikr. By realizing the desire to carry out worship, it is proof that there is dhikr in his heart, because anyone whose heart is negligent will forget to carry out worship; 2). The main key to cleansing the heart is dhikr. Whoever has a clean heart, his soul will feel calm and peaceful, and will automatically become a person with noble character. If the teachings of moral and Sufism education are implemented, it can minimize negative incidents in the form of social deviations that may occur in society, whether at home, village or school. In order to shape students' morals, educators need a process that can be carried out consistently so that students can easily apply moral education.